The impact of economic policy on shipper businesses in coastal line maritime passenger transport in Croatia - Jugović, Alen (Array, 2021)
Coastal line maritime passenger transport in the Republic of Croatia, as well as in other EU member states, is regulated through various regulations and legislation, which in turn result in numerous national laws and regulations that affect its development, all of which is legally binding for shippers. Scheduled maritime passenger transport is an extremely important form of transport for the Republic of Croatia since it is the only form of connection with the mainland for many islands. This paper analyses economic policy measures that affect the organization and implementation of coastal line maritime passenger transport. The paper also investigates the demand fluctuation for maritime passenger transport services. The aid measures provided by the state to individual sectors is also analysed, as well as aid for the provision of services of general economic interest. The aim of this paper is to assess the amount of aid granted to maritime transport and its importance, especially in coastal line maritime passenger transport. The paper also explains the importance of establishing the Coastal Liner Services Agency as a regulatory body of the Republic of Croatia, and it further analyses the subsidy amounts granted to shippers in the period from 2014 to 2020.